Pengaruh Kualitas Pelayanan dan Kepuasan Pasien Peserta BPJS Kesehatan sebagai Mediasi terhadap Loyalitas Pasien - Rosiana Rizal; Muslim Suardi; Yulihasri Yulihasri (Jurnal Sains Farmasi & Klinis, 2017)
The formation of a positive perception of the patient is expected to bring satisfaction in pharmaceutical services, especially drug information services to improve patients’ loyalty to health care services they have used. The design of this research is probability sampling, with a population of patients in public hospitals in Padang city: Dr. M. Djamil Hospital; Dr. Rasidin Hospital; and Dr. Reksodiwiryo Hospital Padang who have used the service of National Health Insurance (BPJS) from January to June 2014. The sampling technique was simple random sampling (105 patients) by using a questionnaire. Data analysis was performed using Cronbach’s alpha analysis, Multiple Regression, R Square, t-test and path analysis. The results of this study indicated that the service quality affected patients’ satisfaction in the dimensions of responsiveness, assurance and direct evidence (p <0.05); toward the loyalty of patients in the direct evidence dimension (p<0.05); and towards patients’ loyalty mediated by patients’ satisfaction in the dimension of direct evidence (p <0.05).